The Challenge of Diagnosing Labyrinthine Stroke—A Critical Review - Alexander A. Tarnutzer; Sun-Uk Lee; Ji-Soo Kim; Diego Kaski (Brain Sciences)
Acute vertigo or dizziness that is accompanied by a sudden sensorineural hearing loss (SSNHL) often poses a diagnostic challenge. While a combined audiovestibular deficit makes an inner ear pathology most likely, this does not necessarily exclude a vascular pathology that may be a harbinger of future sinister events. This is especially true for strokes within the territory of the anterior inferior cerebellar artery (AICA), because the labyrinth receives its vascular supply most often by branches of the AICA. Thus, acute labyrinthine ischemia may present in combination with focal neurologic deficits, but also in isolation or as a warning sign before focal stroke signs arise. How can labyrinthine ischemia be differentiated from an idiopathic SSNHL? In this critical review, we discuss both the pathophysiology and the differential diagnosis of acute audiovestibular deficits. We will also address the value of state-of-the-art MR imaging in visualizing labyrinthine ischemia. Finally, we will discuss treatment options and review the prognosis of acute audiovestibular deficits.